Molecular phylogeny of social vespid wasps inferred from CO1 gene / Norashirene Mohamad Jamil … [et al.] - Mohamad Jamil, Norashirene; Mohamad Jamali, Muhamad Arif; Mohd Yusof, Farida Zuraina; Yaakop, Salmah; Mohd Hatta, Siti Khairiyah (Research Innovation Business Unit, 2014)
In entomology, DNA-based techniques have proven useful in many areas of research, particularly in the study of taxonomic and phylogenetic relationships (Caterino et al., 2000) and population genetics (Behura, 2006). Several gene regions have been used in insect molecular studies (Caterino et al., 2000; Greenstone 2006; Stouthamer, 2006). In this study, COI genes have been chosen as the genetic marker, also known as DNA barcoding. DNA barcoding involves the sequencing of a particular fragment of DNA (generally known as COI gene) a way of identifying an organism. Comparison of the COI sequence for an unidentified and phylogenetic classification of specimen was conducted. As universal primers are used in the initial PCR assay, barcoding can identify new or previously unknown species, cryptic species or strains. In this study, the molecular techniques will be used to clarify phylogenetic relationships among the vespid wasps, focusing on the social vespid wasps in Taman Negara Pahang Kuala Keniam, Kuala Tahan and Krau. One of the remarkable aspects of social vespid wasps is the abundance in its social species, which comprises of three sub-families; vespinae, polistinae and stenogastrinae. Because of their sociality and their relevance as pest species, social Vespidae has received much attention. Colonies of social insects may consist of thousands of individual living in close proximity and characterized by a reduced genetic variability (Barrachi et al., 2012). A molecular systematic study and the contraction of the Vespidae phylogeny on the basis of sequence from the mitochondrial COI gene to construct dendrogram and phylogenetic relationship among the genera in the three subfamilies of social Vespid wasps from Taman Negara Pahang Kuala Keniam, Kuala Tahan and Krau. Identified specimen will be preserved in 95% ethanol. Samples (tissue) been extracted using DNAeasy Tissue Kit (Qiagen), following the DNAeasy protocol. A total of 16 specimens from 3 subfamilies were isolated and 681 basepair of mitochondria COI gene were amplified and sequenced. A solitary wasp of Eumininae was used as outgroup. All the phylogenetic analysed were conducted using Neighbour-Joining (NJ) method performed by MEGA. The conflict between sub-families Stenogastrinae has been solved based on branching pattern of the phylogenetic tree and the genetic distance analysis between the subfamilies. The result show that the sub-families Stenogastrinae form monophyletic pattern with other social vespid wasps.